Antigenicity of phage clones and their synthetic peptides for the serodiagnosis of canine and human visceral leishmaniasis. (September 2017) - Costa, Lourena E.; Salles, Beatriz C.S.; Santos, Thaís T.O.; Ramos, Fernanda F.; Lima, Mariana P.; Lima, Mayara I.S.; Portela, Áquila S.B.; Chávez-Fumagalli, Miguel A.; Duarte, Mariana C.; Menezes-Souza, Daniel; Machado-de-Ávila, Ricardo A.; Silveira, Julia A.G.; et al.
Abstract: In the Americas, Brazil is responsible by 90% of the cases registered of visceral leishmaniasis (VL), and Leishmania infantum is the most common parasite species responsible by disease in Brazilian dogs and humans. A precise diagnosis may allow to a faster and more effective treatment against the disease, which increases the possibility of cure, as well as to induce less toxic effects, due to a lower time exposition for the chemotherapeutics. In a previous study, two L. infantum mimotopes, B10 and C01 clones, were recognized by antibodies in VL dogs sera by a phage display technology, and were well-successfully evaluated as vaccine candidates against visceral and tegumentary leishmaniasis. In the present work, the diagnostic efficacy of these clones, as well as of their exogenous peptides (B10: LSFPFPG and C01: FTSFSPY), was evaluated to diagnose canine and human VL. ELISA assays were performed with the four antigens, and results showed that both clones, as well as their synthetic peptides; showed high sensitivity and specificity values to identify VL samples, presenting an excellent performance to serologically diagnose VL-developing humans and dogs. On the other hand, a wild-type phage, a random non-specific clone and a L. infantum antigenic preparation were used as controls, and showed worst sensitivity and specificity results. In conclusion, besides their biological action as vaccine, B10 and C01 phages and their synthetic peptides could be considered as new markers for the serodiagnosis of canine and human VL. Graphical abstract: Highlights: Two phage clones tested as vaccine were evaluated as diagnostic antigens. Their exogenous peptides were synthesized and also evaluated in ELISA experiments. All antigens showed high sensitivity and specificity values in the assays. They can be used isolate or in association for the diagnosis of visceral leishmaniasis.